The impact of intraoperative neuromonitoring combined with evidence-based nursing on vocal cord function, emotional state, pain, and quality of Life in patients after total thyroidectomy for thyroid cancer: a comprehensive study - Chen, Dandan; Shang, Kun (Frontiers in Oncology, 2025)
ObjectiveTo evaluate the impact of intraoperative neuromonitoring (IONM) combined with evidence-based nursing on vocal function, emotional status, pain levels, and quality of life (QoL) in patients undergoing total thyroidectomy for thyroid cancer.MethodsA single-center randomized controlled trial was conducted. The intervention group received IONM with evidence-based nursing, while the control group underwent IONM with conventional nursing. Outcomes were assessed using the Hospital Anxiety and Depression Scale (HADS), Numerical Rating Scale (NRS) for pain, EORTC QLQ-C30 for 1-month postoperative QoL, and Voice Handicap Index simplified Chinese version (VHI-10) combined with laryngoscopy for vocal recovery and complications.ResultsCompared to controls, the intervention group exhibited significantly lower postoperative VHI-10 scores (5 (2, 8) vs 7 (4, 11), P<0.001), reduced HADS anxiety scores (5 (2, 8) vs 10 (4, 12), P<0.001), and lower 24-hour NRS pain scores (3 (1, 4) vs 4 (2.75, 4.25), P<0.001). The intervention group also demonstrated marked improvements in QLQ-C30 global health status (83 (73.75, 86) vs 77 (72.75, 80), P=0.001), shorter operative duration (92.467 ± 16.916 vs 107.93 ± 24.26 min, P<0.001), reduced intraoperative blood loss (16.5 (9.75, 24) vs 23.5 (11.75, 32) mL, P=0.005), and lower postoperative drainage (59 (30, 77.25) vs 82 (46.5, 110.25) mL, P=0.001).ConclusionThe integration of IONM with evidence-based nursing significantly enhanced postoperative recovery and QoL in thyroid cancer patients. Future studies should prioritize larger cohorts, long-term follow-up, and comparisons across surgical techniques to strengthen clinical recommendations. This multimodal approach demonstrates significant potential for optimizing patient-centered outcomes in thyroid surgery.